Increase in the prevalence of arthritis in adulthood among adults exposed to Chinese famine of 1959 to 1961 during childhood: A cross-sectional survey. Issue 13 (March 2017) - Xu, Xianglong; Liu, Lingli; Xie, Wenxi; Zhang, Yong; Zeng, Huan; Zhang, Fan; Reis, Cesar; Cao, Xianqing; Zhao, Yong
Abstract : Abstract: The developmental origins hypothesis postulates that under-nutrition in the early stage of life is associated with an increased risk of disease in adulthood. This study aimed to examine the association of exposure to the Chinese famine of 1959 to 1961 in early life with the risk of arthritis in adulthood. From July to September 2009, the study adopted multistage stratified random sampling cross-sectional survey to recruit 1224 eligible adults in Chongqing. Famine exposure groups were categorized into 3 groups: (1) childhood exposure, (2) fetal exposure, and (3) nonexposure. Self-reported arthritis of physician diagnosis was obtained. A total of 1224 eligible respondents were interviewed, including 299 individuals exposed during childhood, 455 exposed when fetal, and 470 without exposure. The prevalence of arthritis in adulthood among individuals exposed to famine during childhood was significantly higher than those not exposed (17.39% vs 11.28%, odds ratio [OR] = 1.573 with a 95% confidence interval of [CI] [1.020, 2.424]). Persons exposed to famine during the fetal period did not significantly contribute to a higher rate of arthritis in adulthood than those who were not exposed to famine (13.19% vs 11.28%, OR = 1.072, 95% CI = 0.713, 1.613). In addition, education level, the average monthly income, sleep status, and satisfaction of the present living condition were associated with the risk of arthritis in adulthood. Exposure to the Chinese famine during childhood may be associated with an increased risk of arthritis in adulthood. This study suggests that early life nutrition may have an effect on the risk of arthritis in adulthood.